Microplastics in indoor dust at Dhaka city: unveiling the unseen contaminants within our homes - Haque, Md. Rashedul; Ahmed, Wahida; Islam Rayhan, Md. Rayhanul; Rahman, Md. Mostafizur (Frontiers in Environmental Science, 2024)
Indoor environments, considered sanctuaries from external pollutants, are increasingly recognized as reservoirs for microplastics (MP). This research employed a comprehensive approach, combining dust sampling from diverse indoor spaces, density separation method, and microscopic observation to quantify and characterize microplastic particles. This is the first initial study worldwide that incorporated MP identification in indoor dust from different indoor environments along with factor analysis, health, and ecological risk assessment. The average MP concentration in the indoor environment was 4333.18 ± 353.85 MP/g. The MP distribution pattern was in institutional areas < residential areas